Phyto/rhizoremediation studies using long-term PCB-contaminated soil - Mackova, Martina; Prouzova, Petra; Stursa, Petr; Ryslava, Edita; Uhlik, Ondrej; Beranova, Katarina; Rezek, Jan; Kurzawova, Veronika; Demnerova, Katerina; Macek, Tomas (Environmental science and pollution research international, 2009)
PURPOSE: Polychlorinated biphenyls (PCBs) represent a large group of recalcitrant environmental pollutants, differing in the number of chlorine atoms bound to biphenyl ring. Due to their excellent technological properties, PCBs were used as heat-transfer media, for filling transformers and condensers, as paint additives, etc. With increasing knowledge of their toxicity, transfer to food chains and accumulation in living organisms, their production ended in most countries in the 1970s and in 1984 in the former Czechoslovakia. But even a quarter of century after the PCB production ceased, from contaminated areas, the volatile PCBs evaporate and contaminate much larger areas even at very distant parts of the world. For this reason, PCBs still represent a global problem. The main method of PCB removal from contaminated environment is at present the expensive incineration at high temperatures. With the aim of finding effective alternative approaches, we are studying biological methods for PCB removal from the environment. In this paper, we summarise 10 years of studies using long-term PCB-contaminated soil from a dumpsite in South Bohemia, targeted for the use of plants (phytoremediation) and their cooperation with microorganisms in the root zone (rhizoremediation). MATERIALS AND METHODS: Long-term contaminated soil from Lhenice dumpsite, more than hundred kilograms of homogenised material, was used in microcosms (pots and buckets), and field plots were established at the site. Tested plants include among others tobacco, black nightshade, horseradish, alfalfa and willow. Aseptic plant cell and tissue cultures were from the collection of the IOCB. Microorganisms were our own isolates. The paper summarises experiments done between 1998 and 2008 with real contaminated soil, both vegetated and non-vegetated. PCB analysis was performed by GC-ECD, metabolic products identified mostly using 2D-GC/MS-MS and synthetic standards, whereas molecular methods included quantitative PCR and sequencing. RESULTS: The soil was used both for preparation of field plots at the site and for greenhouse and laboratory tests in microcosms. The results include analyses of changes in PCB content in untreated and vegetated soil, PCB uptake and distribution in different parts of various plant species, analysis of products formed, identification and characterisation of cultivable and non-cultivable bacteria both in rhizosphere and in bulk soil. Different treatments and amendments were also tested. Experiments in real contaminated soil were accompanied by in vitro experiments using aseptic cultures of plant biomass, genetically modified (GM) plants and bacteria, to allow identification of players responsible for PCB metabolisation in soil. The time-span of the experiments allows extrapolating some of the results and drawing conclusions concerning the effectivity of exploitation of various plant species and treatments to remove PCBs from soils. DISCUSSION: The approach using plants proved to represent a viable alternative to costly incineration of PCB-contaminated soils. The recent studies using molecular methods show that plants are responsible for the composition of consortia of microorganisms present in their root zone, including those with ability to degrade the chlorinated aromatic compounds. CONCLUSIONS: In addition to uptake, accumulation and partial metabolisation of PCBs by plants, compounds produced by plants allow survival of microorganisms even in poor soils, serve as carbon and energy source, and can even induce the degradation pathways of different xenobiotics. Thus, the choice of proper plant species is crucial for effective cleaning of different polluted sites. Our study shows how the efficiency of PCB removal is dependent on the plant used. RECOMMENDATIONS AND PERSPECTIVES: The use of plants in biological remediation of different organic xenobiotics proved to be a useful approach. Further improvement can be expected by application of specifically tailored GM plants and use of selective conditions ensuring high remediation potential based on optimal composition of the soil microbial consortia designed for the needs of given site.
Keywords: kořeny rostlin; Biodegradation, Environmental; biodegradace; rostliny; Soil Pollutants; Soil Microbiology; Polychlorinated Biphenyls; Time Factors; látky znečišťující půdu; Plant Roots; půdní mikrobiologie; Soil; půda; Plants; polychlorované bifenyly; časové faktory